Pelatihan Peningkatan Kemampuan Komunikasi Bisnis Kelompok Usaha BersamaÂ Ibu-Ibu PKK Desa Tempeh Lor Kecamatan Tempeh - Yatminiwati, Mimin (IMPOWERMENT SOCIETY, 2018)
Good and proper communication is very important to be done by an entrepreneur. Communication is the activity of delivering, receiving and processing messages from one person to another. Communication is closely related to the sensory system. Example: hearing. The ability to communicate can be called as the ability to speak because the language is used as a language communications. Therefore, the authors feel the need to provide training Improvement of Business Communication Skills Business Group with Mother PKK Tempeh Lor Village District Tempeh Year 2017.